AAFD Staging System: Did We Get It Right?. Issue 3 (September 2019) - Li, Shuyuan; Yao, Lufeng; Myerson, Mark S.
Abstract : We present here an evolution of thinking of various classification systems that have been used to approach treatment of the adult flatfoot deformity. While the current popular classification is clinically useful, it is far from satisfactory. There are still too many outliers, and for any classification system to work, it must be applicable to all deformities, and all patients. We describe clinical as well as patient parameters which do not fit in with the current classification scheme, and make recommendations for future study.